The Implementation of Father and Son Story in The Al Qur'an in The Family Character Education - Radhiatul Hasnah; Rezki Amelia; Gusmirawati Gusmirawati; Inong Satriadi; Marhamah Marhamah (Ta'dib, 2022)
Morals is influenced by both education and the process of religious values internalizing to the children.┬á The foundations of moral education is the obligation of parents and it is also the duty of teachers, society, and the government through various educational institutions. This article also examines the verses of the Qur'an relating to an educational approach based on the story of father and son that later can be used to teach the children character in their family. One of the main tasks of a parents is to teach their children moral education beside people who they live with, teachers, and government. This paper discusses the learnings found in the Qur an, the story of Father and their Sons and discuss how it contribute a family character education. This research was categorized a descriptive qualitative, described the history of a Father and his son in the QurÔÇÖan and how it should be implemented in a family moral education. The techniques of collecting the data were interview and observation.┬á The findings show the role of father use several approaches in teaching his children which are still relevant with the current context. These approaches include experiential approach, the habituation approach and the emotional approach.┬á Several families that became the object of research have implemented the three approaches.